Health care needs of persons affected by leprosy in Kurnool division of Kurnool district - Guthi, Visweswara Rao; Sreedevi, A. (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the challenges in NLEP-3 is need assessment as well as establishment of well-coordinated services with capacity building for prevention and care of disabilities due to leprosy at primary, secondary and tertiary levels in the country. There is very little data on the types of problems faced by people with leprosy-related disabilities (PLD) and the resulting needs. Aim of the study is to assess the health care needs of study subjects. Methodology: This is a community based cross–sectional study conducted in Kurnool district. There were 296 registered persons affected by leprosy between May 2012 to October 2013 out of which 276 registered persons affected by leprosy were available for the study. Information collected was place of registration for availing MDT, treatment status, mode of detection, health care provider consulted first etc. Results: 48.55% of all the registered cases reported voluntarily. (36/276) 13.05% of cases were detected during consultation for other general ailments and 8.69% were detected by health worker during routine field visit. Health worker provided MDT to the persons affected by leprosy at their houses in 14.49% of the cases, 85.51% of the persons obtained MDT from the treatment centre themselves. Conclusions: This study concluded that there was encouraging to note that public health system was the predominant health system for seeking health care. Most of the cases reported voluntarily to the health care facility. Majority was aware that leprosy causes deformities but did not know that deformities can be prevented.